The role of COVID‐19 survivor status and gender towards neutralizing antibody titers 1, 2, 3 months after Sinovac vaccine administration on clinical‐year medical students in Indonesia - Rivaldo Steven Heriyanto; Andree Kurniawan; Felix Wijovi; Devina Adella Halim; Claudia Jodhinata; Elizabeth Marcella; Billy Susanto; Johan Wibowo; Michele Indrawan; Nadia Khoirunnisa Heryadi; Michelle Imanuelly; Jonathan Juniard Anurantha; et al. (International Journal of Infectious Diseases, 2021)
Background: Sinovac was the first vaccine used in Indonesia against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, data regarding the effects of certain variables such as clinical demographics on antibody levels in individuals vaccinated with Sinovac are scarce. This study aimed to investigate the impact of gender and previous SARS-CoV-2 infection status on neutralizing antibody titers 1, 2, and 3 months after administration of the Sinovac vaccine.Method: A cross-sectional study was conducted from February to May 2021. Data on neutralizing antibody levels, previous SARS-CoV-2 infection status, and gender were retrieved from the monthly quantitative serology evaluation database of Siloam Hospitals Lippo Village, Tangerang, Indonesia. The role of each variable was analyzed using the t-test or Mann-Whitney U test, depending on data distribution.Result: Data from 350 participants were collected for the study. Participants with a history of a positive SARS-CoV-2 RT-PCR test had significantly higher neutralizing antibody titers in the first (144 U/mL, p = 0.036) and second months (144 U/mL, p = 0.005) after vaccination compared with those without a history of positive RT-PCR test. Female participants also had significantly higher neutralizing antibody titers in the first, second, and third months (43 U/mL, 42 U/mL, and 39 U/mL, respectively; p = 0.001, p = 0.002, and p = 0.003, respectively) after vaccination compared to males.Conclusion: COVID-19 survivor status and the female gender were associated with higher neutralizing antibody titers after Sinovac vaccine administration.